Proposal of competencies for engineering education to develop water infrastructure based on "Nature-Based Solutions" in the urban context. (20th August 2020) - Vera-Puerto, I.; Valdes, H.; Correa, C.; Agredano, R.; Vidal, G.; Belmonte, M.; Olave, J.; Arias, C.
Abstract: The aim of this work was to determine the competencies that need to be included in engineering programs to develop water infrastructure based on Nature-Based Solutions (NBS) in the urban context, focused on its application in developing countries. Thus, the work was developed in three phases: i) a theoretical phase, ii) a validation phase and iii) a statistical analysis. For the theoretical phase, a literature review was conducted to determine a set of competencies for developing these type of projects. Next, in the validation phase, fifty participants were invited to complete a two-round Delphi questionnaire to rank the competencies detected in the literature review. The participants were classified according to their level of knowledge ( skilled or expert ) and place of work (countries with upper-middle-income or high-income ). The results showed that twenty-one competencies were identified. In the validation phase, for the first Delphi round, the different groups studied ( skilled vs expert ; high-income vs upper-middle - income ) did not agree about the most important competencies. However, after the second Delphi round, an agreement was achieved. Therefore, competencies related to water quality and process design for improving its quality were defined as "extremely important" competencies. In addition, the entire panel of experts also highlighted competencies related to legislation, circular economy, equipment, climate, and construction materials. Thus, for the first time, a set of competencies that needs to be included in educational programs for engineers with a special focus on developing water infrastructure based on NBS in the urban context of developing countries has been proposed in this work. Highlights: Twenty-one competencies were established to train engineers in Nature-Based Solutions. Established competencies guide engineering education to urban water infrastructure. Water quality knowledge was the most important competency for engineering education. Experts reached consensus after second round of Delphi methodology.